Applying SOFL to Enhance Requirements Gathering in Educational Technology: Case Study of Developing Course Plan Assistant - Abdul Rahman, Mat; Edwin, Mit; Ayu Nazirah, Razamie (IEEE, 2026)
The purpose of this research paper is to present the approach of applying the Structured Object-oriented Formal Language (SOFL) method for requirements gathering in the development of a Course Plan Assistant (CPA). This system aimed at efficiently tracking and enhancing students’ academic progress. The study adopts the case study methodology, focusing on the design and implementation of the CPA. The SOFL method is employed to systematically gather and document the requirements for the development of the system. This includes a detailed analysis and modeling of the educational context, stakeholder requirements, and system functionalities. The findings of the research indicate that the SOFL method significantly improves the clarity and completeness of the requirements gathering process. It facilitates better communication and understanding among stakeholders, leading to the identification of key features that enhance student progress tracking. The study demonstrates that the use of SOFL reduces ambiguities and misunderstandings during the requirements elicitation phase. This research contributes to the literature by providing insights into the application of the SOFL method within an educational context. It highlights the importance of a structured and rigorous approach in requirements gathering for systems aimed at improving academic performance. The findings of this case study can serve as a reference for future projects in educational technology and requirement engineering.